Social Movements, Collective Identity, and Workplace Allies: The Labeling of Gender Equity Policy Changes - Wang, Cynthia S.; Whitson, Jennifer A.; King, Brayden G; Ramirez, Rachel L. (Organization Science, 2023)
Social movements seek allies as they campaign for social, political, and organizational changes. How do activists gain allies in the targeted institutions they hope to change? Despite recognition of the importance of ally support in theories about institutional change and social movements, these theories are largely silent on the microdynamics of ally mobilization. We examine how the labeling of organizational policies that benefit women influences potential workplace allies’ support for these policies. We theorize that one barrier to mobilizing workplace allies is a misalignment of the labels that activists use to promote new policies and employees’ affiliation with collective identities. We conducted five experiments to test our hypotheses and 26 qualitative interviews to provide illustration of our core concepts. We demonstrate that employees high in feminist identification are more likely to support feminist-labeled (feminist and #MeToo) than unlabeled policies, whereas those low in feminist identification are less likely to support feminist-labeled than unlabeled policies (Studies 1–3). However, we find that participants for whom organizational identification was high (whether measured or manipulated) and feminist identification was low supported organizationally labeled policies more than feminist-labeled polices (Studies 4 and 5). This illustrates that policies whose aims may not align with one collective identity can still garner support by activating another relevant collective identity. Within our studies, we provide evidence that these effects are mediated via feelings of pride in the organization (and not fear or anger), suggesting that positive emotions are a central mechanism in mobilizing workplace allies. History: This paper has been accepted for the Organization Science Special Issue on Experiments in Organizational Theory. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.1492 .